Electrical Discharges with Liquid Electrodes Used in Water Decontamination; High Temperature; Vol. 52, iss. 4 - Son E. E. Eduard Evgenevich; Suvorov I. F. Ivan Flegontovich; Kakaurov S. V. Sergey Vladimirovich; Gaysin A. F. Almaz Fivzatovich; Samitova G. T. Gulnara Torekul'evna; Solovjeva T. L. Tatjyana Leonidovna; Yudin A. S. Artem Sergeevich; Rakhletsova T. V. Tatyana Vladimirovna (2015, 2015)
Title screen